Nitrous oxide in the North Atlantic Ocean - Walter, S.; Bange, H. W.; Breitenbach, U.; Wallace, D. W. R. (CCSD, 2006)
International audience In order to get a comprehensive picture of the distribution of nitrous oxide (N 2 O) in the North Atlantic Ocean, measurements of dissolved nitrous oxide were made during three cruises in the tropical, subtropical and cold-temperate North Atlantic Ocean in October/November 2002, March/April 2004, and May 2002, respectively. To account for the history of atmospheric N 2 O, we suggest a new depth-dependent calculation of excess N 2 O (?N 2 O). N 2 O depth profiles showed supersaturation throughout the water column with a distinct increasing trend from the cold-temperate to the tropical region. Lowest nitrous oxide concentrations, near equilibrium and with an average of 11.0±1.7 nmol L ?1 , were found in the cold-temperate North Atlantic where the profiles showed no clear maxima. Highest values up to 37.3 nmol L ?1 occurred in the tropical North Atlantic with clear maxima at approximately 400 m. A positive correlation of nitrous oxide with nitrate, as well as excess nitrous oxide with the apparent oxygen utilization (AOU), was only observed in the subtropical and tropical regions. Therefore, we conclude that the formation of nitrous oxide via nitrification occurs in the tropical region rather than in the cold-temperate region of the North Atlantic Ocean